IOT-Based automated feeding fish system using : NodeMCU / Afandi Asqalani Abdul Azis - Abdul Azis, Afandi Asqalani (2020)
It has become our responsibility as a person to take care of a fish who keep it as a pet. As a fish keeper, we must know and take care of the nutrition and diet of the fish where we must feed the fish on a daily basis. The problem occurs when a fish keeper cannot give proper care of the fish because they are too busy with their work and often forget to feed their fish. Because of this matter, there is an urgent need for innovation, so the aim of this paper is to assist fish keeper to feed the fish on schedule on the daily basis by using microcontroller Node MCU ESP8266. The result through this design, the Automated Feeding Fish System can help aquarist to feed the fish by controlling the servo motor via WIFI connection. Other than that, this design also helps the fish keeper check the measurement of the water to know the right quality of water for the fish by using a turbidity sensor. So, the fish keeper knows when to change the water in the aquarium so it can restore and maintain the quality of life in the aquarium. Even though the system can achieve the user expectation there is lot areas need to be improved. Hopefully, the study can make the improvement of feeding fish and help the fish keeper to become much better in taking care of the fish.